Long-term orange juice consumption is associated with low LDL-cholesterol and apolipoprotein B in normal and moderately hypercholesterolemic subjects - Aptekmann, Nancy P. [UNESP]; César, Thaís Borges [UNESP] (Springer Nature, 2013)
Abstract. Background: This study investigated the hypothesis that long-term orange juice consumption (≥ 12 months) was associated with low risk factors for cardiovascular disease in adult men and women with normal and moderately high cholesterol blood levels. Methods. The sample consisted of 103 men (18-66 y) and 26 women (18-65 y); all were employees of an orange juice factory with daily access to free orange juice. The results showed that 41% of the individuals consumed 2 cups (480 mL) of orange juice per day for at least twelve months, while 59% of the volunteers are non-consumers of orange juice. Results: Orange juice consumers with normal serum lipid levels had significantly lower total cholesterol (-11%, p <0.001), LDL-cholesterol (-18%, p < 0.001), apolipoprotein B (apo B) (-12%, p < 0.01) and LDL/HDL ratio (-12%, p < 0.04) in comparison to non-consumers, as did the consumers with moderate hypercholesterolemia: lower total cholesterol (-5%, p <0.02), LDL-cholesterol (-12%, p <0.03), apolipoprotein B (-12%, p <0.01) and LDL/HDL ratio (-16%, p <0.05) in comparison the non-consumers counterparts. Serum levels of homocysteine, HDL- cholesterol and apolipoprotein A-1, body composition and the dietary intake of food energy and macronutrients did not differ among orange juice consumers and non-consumers, but vitamin C and folate intake was higher in orange juice consumers. Conclusion: Long-term orange juice consumers had lower levels of total cholesterol, LDL-cholesterol, apo B and LDL/HDL ratio and an improvement of folate and vitamin C in their diet. © 2013 Aptekmann and Cesar; licensee BioMed Central Ltd.
Keywords: Apo B; Homocisteína; Homocysteine; Humanos; Humans; LDL-cholesterol; Orange juice; Suco de laranja LDL-colesterol; apolipoprotein A1; apolipoprotein B; ascorbic acid; carbohydrate; folic acid; high density lipoprotein cholesterol; homocysteine; low density lipoprotein cholesterol; saturated fatty acid; adult; aged; body composition; caloric intake; carbohydrate intake; cholesterol blood level; controlled study; fat intake; female; food intake; human; human tissue; hypercholesterolemia; macronutrient; major clinical study; male; orange juice